The Heartland - Mclaughin, Robert (New York : Time incorporated, 1967)
This report provides a Latino-focused assessment of the changing demographic and economic landscape of the Midwest between 1980 and 1990. Over 56 percent of the region's population increase was accounted for by Latinos, of which persons of Mexican origin were the largest proportion. The White population decreased by over 300,000 persons, with the remainder of the growth evenly divided between Blacks and "other." Illinois, particularly the Chicago area, showed the most Latino growth, with Michigan second. Whites, Blacks, and Latinos all experienced income declines, but Whites lost the least, followed by Latinos, and Blacks. Nearly a third of the region's Blacks were in poverty, over 1 in 5 Latinos were poor, while less than 1 in 10 Whites were impoverished. Among Latinos, Puerto Ricans showed poverty rates equal to Blacks. Latinos trailed all others on educational attainment indicators, despite the fact that Latino labor force participation exceeded that of Whites and Blacks. Although median household income of Latinos was higher than that of Blacks, it was less than that of Whites. Because of larger household size among Latinos, the per capita income for Latinos and Blacks was about equal. Research is needed to determine what factors accounted for the disproportionate downturn in income for Blacks and Latinos. Frequently broken down by state, Midwest demographics based on census figures are depicted in 34 tables and 36 figures. (TD)
Microfiche.
Keywords: Census Figures; Demography; Economic Change; Educational Attainment; Employment Patterns; Ethnic Distribution; Immigrants; Income; Mexican Americans; Population Growth; Poverty; Social Indicators; Socioeconomic Status; Latinos -- United States (Midwest); Numerical/Quantitative Data; Reports, Research